A Case of Mysterious Poisoning - Maria Sheakley; Charles Seidel; Alan Ernst; Aidi Yin (Association of American Medical Colleges, 2008)
Abstract Introduction As the National Board of Medical Examiners shelf exams and the United States Medical Licensing Examination Step One exam are becoming more clinically oriented, the introduction of cases to first-year medical students is becoming more important. Thus, this case was written as a joint effort by faculty members from the departments of physiology, anatomy (histology), and neuroscience as an integrated case for first-year medical students in a team-based learning format. Methods The case provides basic clinical information about neuromuscular histology and physiology, which students are introduced to in weeks six through eight of the semester. The questions at the end of the case were written to stimulate group discussion. Results The case generated more than 30 minutes of small-group and class discussion amongst the students in the course, and evoked true interest in the topic area. Students surveyed after the session gave overwhelming positive feedback about the case and the class discussion it generated. Discussion Small-group clinical case work promotes student interaction and discussion, as well as increased retention of knowledge and enhanced student interest.